Bioaminergic Responses in an In Vitro System Studying Human Gut Microbiota–Kiwifruit Interactions - Shanthi G. Parkar; Carel M. H. Jobsis; Tania M. Trower; Janine M. Cooney; Duncan I. Hedderley; Kerry L. Bentley-Hewitt (Microorganisms, 2020)
Whole kiwifruit (‘Hayward’ and ‘Zesy002’) were examined for their bioaminergic potential after being subjected to in vitro gastrointestinal digestion and colonic fermentation. Controls included the prebiotic inulin and water, a carbohydrate-free vehicle. The dopamine precursor l-dihydroxyphenylalanine (L-DOPA) and the serotonin precursor 5-hydroxytryptophan were increased in the kiwifruit gastrointestinal digesta (‘Hayward’ > ‘Zesy002’) in comparison to the water digesta. Fermentation of the digesta with human fecal bacteria for 18 h modulated the concentrations of bioamine metabolites. The most notable were the significant increases in L-DOPA (‘Zesy002’ > ‘Hayward’) and γ-aminobutyric acid (GABA) (‘Hayward’ > ‘Zesy002’). Kiwifruit increased Bifidobacterium spp. and Veillonellaceae (correlating with L-DOPA increase), and Lachnospira spp. (correlating with GABA). The digesta and fermenta were incubated with Caco-2 cells for 3 h followed by gene expression analysis. Effects were seen on genes related to serotonin synthesis/re-uptake/conversion to melatonin, gut tight junction, inflammation and circadian rhythm with different digesta and fermenta from the four treatments. These indicate potential effects of the substrates and the microbially generated organic acid and bioamine metabolites on intestinal functions that have physiological relevance. Further studies are required to confirm the potential bioaminergic effects of gut microbiota–kiwifruit interactions.